Perbedaan Efektifitas Pemberian Yoga dan Kompres Hangat Terhadap Tingkat Nyeri Dismenore Pada Mahasiswa Fakultas Ilmu Kesehatan Universitas Kadiri Tahun 2019 - Sutrisni, Sutrisni; Arfiani, Arfiani (Universitas Nusantara PGRI Kediri, 2020)
Dismenorrea is a pain during menstruation that interferes with a woman's daily activities and encourages sufferers to have an examination or consultation with a doctor, or come obstetrics. Based on preliminary studies, the number of students experiencing menstrual pain (dysmenorrhea) was 89.1% greater than the number of students who did not experience menstrual pain (dysmenorrhea) of 10.8%. The goal is to analyze the Difference in Effectiveness of Giving Yoga And Warm Compresses to The Level of Dismenor Pain in Students of Faculty of Health Sciences Unversitas Kadiri in 2019. sampling in research using purposive sampling methods. This research is pre experimental. The sample in this study was 32 people. This research was conducted at the Faculty of Health Sciences of Kadiri University in August 2019. Analyze data on comparative hypothesis tests using paired, ratio-shaped data. The study used paired t test and Wilcoxon Signed Rank Test. The results showed there was an influence of Yoga and warm compresses on the decrease in menstrual pain in students of the university's faculty of health sciences kadiri in 2019. Mann-Whitney's different test results showed that p 0.047 < α (0.05) so that H1 received H0 was rejected which meant there was a difference in the effectiveness of Yoga and warm compresses where warm compresses were more effective than Yoga against a decrease in the menstrual pain scale in students of the university's faculty of health sciences kadiri in 2019.